Robust Fault Detection for Discrete‐Time Nonlinear Impulsive Switched Systems. Issue 1 (19th July 2016) - Li, Jian; Song, Zhengfan; Su, Qingyu
Abstract: This paper deals with the problem of robust fault detection for discrete‐time nonlinear impulsive switched systems. The fault detection filter is used as the residual generator, in which the filter parameters are dependant on the system mode. Attention is focused on designing the robust fault detection filter. The problem of robust fault detection is converted into an H ∞ ‐filtering problem. A sufficient condition for the solvability of this problem is established by a convex optimization problem. A numerical example is provided to demonstrate the effectiveness of the proposed method.